Student expectations of peers in academic asynchronous online discussion - Dianne Forbes (Flexible Learning Association of New Zealand, 2022)
In open, flexible, and distance learning, asynchronous online discussion persists as a popular means of interaction and collaboration. The research literature abounds with consideration of instructor roles and expectations of teachers and tools. Student-to-student interaction is widely acknowledged as a salient benefit of asynchronous online discussion, with implications for collaborative learning and problem-solving, as well as student satisfaction and course commitment. But what do students expect of their peers when communicating online for learning purposes? This question has seldom been considered, despite common reliance on peer-to-peer learning interactions. This small-scale case study incorporates an online focus group and semi-structured interviews with second-year undergraduate students studying primary teaching in Aotearoa New Zealand. The students in this study expect responsive, free-flowing contributions by peers, culminating in discussion that is active and interactive. Given the imperative to value student experience and to involve students in active learning, it is timely to share peer expectations so that students are accountable to their class community and are better prepared for collaborative learning through asynchronous online discussion.